Gene and cell therapy and nanomedicine for the treatment of multiple sclerosis: bibliometric analysis and systematic review of clinical outcomes. (3rd April 2021) - Caballero-Villarraso, Javier; Sawas, Jamil; Escribano, Begoña M.; Martín-Hersog, Francisco A.; Valverde-Martínez, Andrea; Túnez, Isaac
ABSTRACT: Introduction: Continuous improvement in cellular and molecular biology has led to the development of diverse advanced therapies. These include cell therapy and gene therapy, among others. Nanomedicine can also be used for therapeutic purposes. Areas covered: The author carried out a bibliometric analysis to find out about the biomedical literature in these therapies applied to multiple sclerosis (MS) and its chronological evolution, from a quantitative and qualitative point of view. After this, articles which were identified as clinical trials were retrieved full-text and examined for further evaluation of their evidence-based level according to the CASP scale. In the bibliometric analysis the authors retrieved 2, 791 studies, from which 2, 405 were about cell therapy, 194 about gene therapy and 192 about nanomedicine; scientific production in these areas has been progressive and growing in terms of quantity and quality. In the systematic review 39 trials were retrieved, all of them about cell therapy, which had relevant sample sizes. The average of scientific-quality was good or very good (about 9/11 points). Expert opinion: There is a class I evidence supporting the effectiveness of cell therapy as safe therapeutic option in multiple sclerosis with health benefits in the medium and long term.